Motivators for using on-demand vehicle sharing services in Brazil - Violin, Fábio [UNESP] (Fucape Business School, 2022)
This study focused on the analysis of motivators for the use of on-demand travel modes in Brazil. The methodological procedures included the use of combined methods of probabilistic sampling and pre-tests to design the research instrument and use of the IBM SPSS Statistics software, for data treatment which used, among others, exploratory and confirmatory factor analysis. The five major regions of Brazil were considered in this research, totaling 2150 interviews, indicating the existence of fourteen motivators for use involving the economic, social, environmental, and technological dimensions, however, only six variables comprise the structuring nucleus of demand and are based on an element of economic order (Reduced Tariff), one of a socioeconomic nature (Expectation of Benefits) and four technological drivers (Technological Availability, Convenience of Time and Boarding in addition to Data Security), which figure as utilitarian indicators, corroborating the results of international studies and contrasting those that signal hedonistic elements as relevant. In this sense, the study presents advances in establishing parameters of consumer choice based on the use of platforms aimed at displacement, figuring as an indicator of the reasons for use and their scaling of relevance in the users’ decision-making process.
Keywords: Consumer Behavior; Sharing Economy; Technology